The effect of Alternate Nostril Breathing (ANB) on blood pressure dynamics in hypertensive patients - Muh. Anwar Hafid; Nurul Hidayati (Universitas Aisyiyah Yogyakarta, 2026)
Hypertension is a major public health problem that requires safe and affordable non-pharmacological support. Alternate Nostril Breathing (ANB) may help reduce blood pressure by promoting autonomic balance, but its serial effects across repeated sessions remain limited. This study aimed to examine the effect of ANB on blood pressure dynamics in hypertensive patients. A pre-experimental one-group pretest–posttest design was used. Twenty-five hypertensive patients were selected purposively and received one supervised ANB session daily for seven consecutive days. Blood pressure was measured at baseline and after each session. Data were analyzed using repeated-measures ANOVA. The respondents were all women, mostly aged 56–60 years, with low educational attainment, and most were housewives. Mean systolic blood pressure decreased from 154.68 mmHg at baseline to 139.20 mmHg at Post 7, while mean diastolic blood pressure declined from 97.28 mmHg to 83.12 mmHg. All comparisons showed significant reductions across the intervention period. ANB was associated with a progressive and significant reduction in blood pressure among hypertensive patients (p-value <0.05). ANB may be considered a simple, low-cost complementary intervention in primary health care, and future studies should use controlled designs with larger samples and longer follow-up to confirm its effectiveness.